Respon pertumbuhan vegetatif padi varietas IPB 4S pada kondisi cekaman kekeringan - Nasrudin Nasrudin; Efrin Firmansyah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Drought stress affected growth and decreases rice yield. The use of high yielding varieties and drought tolerance is a strategic step that can be applied during drought stress. The aim of this research was to examine the response of the growth of IPB 4S rice varieties on planting media with drought stress during vegetative phase. The research used a nonfactorial Completely Randomized Design with six levels: field capacity, 10% of field capacity, 20% of field capacity, 30% of field capacity, 40% of field capacity, and 50% of field capacity. The treatments were repeated three times. The growth parameters were plant high, number of tiller, leaf color, leaf area, root length, root dry weight, canopy dry weight, and biomass. The results showed that the drought stress significantly different to leaf area, root length, canopy dry weight, and biomass but were not significantly different to plant height, number of tiller, leaf color, dan root dry weight. Increased of drought stress 30 to 50% of field capacity decreased of leaf area, canopy dry weight, and biomass, but increased root length.